CROMOLYN INHIBITS 7, 12-DIMETHYLBENZ (A) ANTHRACENE INDUCED ORAL CANCER THROUGH APOPTOTIC INDUCTION AND SUPPRESSION OF CELL PROLIFERATION - SEKAR KARTHIKEYAN; SHANMUGAM MANOHARAN (International Journal of Pharma and Bio Sciences, 2016)
The present study evaluated the effect of cromolyn on the expression pattern of genes involved in the process of apoptosis (P53, Bcl-2, Bax, Bcl-xL and Bad) and cell proliferation (PCNA, Cyclin D1, CDK4, CDK6 and Survivin) during 7,12-dimethylbenz(a)anthracene (DMBA)induced hamster buccal pouch carcinogenesis. Hamsters buccal pouches exposed to 0.5% DMBA in liquid paraffin, three times a week for 14 weeks, developed well differentiated squamous cell carcinoma. Administration of cromolyn at a dose of 80mg/kg b.w orally to hamsters treated with DMBA not only prevented the tumor formation but also induced apoptosis and suppressed cell proliferation. Thus, the apoptotic and anti-cell proliferative efficacy of cromolyn might have suppressed DMBA induced tumorgenesis in the buccal pouches of golden Syrian hamsters